2023
DOI: 10.3390/plants12040792
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with Oidiodendron maius BP Improves Nitrogen Absorption from Fertilizer and Growth of Vaccinium corymbosum during the Early Nursery Stage

Abstract: Blueberry roots are inefficient in taking up water and nutrients, a fact partially related to their scarcity of root hairs, but they improve nutrient uptake by associating with ericoid mycorrhizal and endophytic fungi. However, the benefits of this association are both cultivar- and fungus-dependent. Our objective was to assess the effect of inoculation with three native fungal strains (Oidiodendron maius A, O. maius BP, and Acanthomyces lecanii BC) on plantlet growth, plantlet survival, and nitrogen (N) absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…The work of Pescie et al [20] analyzed the effect of the inoculation of Oidiodendron maius A, O. maius BP, and Acanthomyces lecanii BC on the growth and survival of the seedlings of two southern high blueberry cultivars. It was found that O. maius BP had a positive effect on the N content and the plant biomass of both blueberry varieties, while O. maius A improved plant survival.…”
Section: Special Issue Contentsmentioning
confidence: 99%
“…The work of Pescie et al [20] analyzed the effect of the inoculation of Oidiodendron maius A, O. maius BP, and Acanthomyces lecanii BC on the growth and survival of the seedlings of two southern high blueberry cultivars. It was found that O. maius BP had a positive effect on the N content and the plant biomass of both blueberry varieties, while O. maius A improved plant survival.…”
Section: Special Issue Contentsmentioning
confidence: 99%
“…Barron (1962) (Myxotrichaceae, Leotiomycetes) is one of the main fungi of ericoid mycorrhiza. Its mycorrhiza-associated development in plant roots has been repeatedly confirmed with culture-dependent and/or culture-independent methods in Vaccinium myrtillus L. [6,7], V. uliginosum L., V. corymbosum L. [8,9], and other heather species [3,10,11]. As a model organism, O. maius is used to study mycorrhiza evolution, organization, and functioning, as well as mechanisms of heavy metals tolerance [6,7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…y Lachnum sp. (Bizabani y Dames, 2015) se han identificado en las células rizodérmicas de plantas ericáceas sanas formando la micorriza ericoide, caracterizada por la presencia de finas bobinas de hifas intracelulares (Read, 1996) encargadas de conferir beneficios, como una mejor adquisición de nutrientes minerales (Pescie et al, 2023) y el alivio de estrés por sequía (Mu et al, 2021), entre otros. También destaca su asociación con hongos endófitos septados oscuros, como Phialocephala fortinii, con capacidad de liberar enzimas capaces de disolver nutrientes insolubles como el fósforo (Daghino et al, 2022) o algunos hongos de la división Basidiomicota, destacando algunos Sebacinales (Vohník et al, 2016).…”
Section: Introductionunclassified